Emperor Mage - Pierce, Tamora (New York : Simon Pulse, 2005)
When she is sent as part of the delegation from Tortall to negotiate a peace treaty with Carthak, fifteen-year-old Daine must use her powers to communicate with animals for more than healing the Carthak emperor's dying birds.
Keywords: Sarrasri, Daine (Fictitious character) -- Fiction; Human-animal communication -- Fiction; Supernatural -- Fiction; Fantasy; Sarrasri, Daine (Fictitious character) -- Juvenile fiction; Human-animal communication -- Juvenile fiction; Supernatural -- Juvenile fiction; Fantasy fiction